Numerical Study of Hydrodynamic Performance of a Hydrofoil with Vibration Trailing Edge. (June 2020) - Xu, Yingbo; Tang, Denghai
Abstract: In order to study the influence of trailing edge vibration to the hydrodynamic performance of hydrofoil, the large eddy simulation and moving wall boundary condition methods were used to simulate the flow field of NACA66-mod hydrofoil with different trailing edge vibration amplitude(VA) and frequency. First, the numerical simulation methods are verified by comparing with experimental data. Then the flow field of hydrofoil was simulated to study the influence of vibration frequency and amplitude to hydrodynamic performance. The result shows that the vibration amplitude and frequency has significantly influence on the trailing edge vortex shedding. The intensity of the vortex increases rapidly with the vibration amplitude increasing. The lift and drag coefficients are influenced by the vibration amplitude and frequency.